The impact of hotel quality dimensions and hotel image on the behavioral intentions: Mediating role of memories - Rukh, Lala; Abid, Dr. Ghulam; Nisar, Asma; Ali, Syed Adnan (The journal of contemporary issues in business and government, 2021)
This study is first to evaluate the role of memories in the hospitality and tourism industry of Pakistan. The mediating role of memories in the relationship of staff presentation and knowledge, and hotel image on customers’ behavioral intentions has been investigated in luxury hotel settings. The respondents of the study are customers of the hotel industry. The data has been collected from 354 respondents through convenience sampling technique. Data was analyzed through PLS-SEM. Findings show that memories play a role in increasing behavioral intentions of the customers. Theoretical and practical implications are discussed in detail.